2016
DOI: 10.1186/s12906-016-1276-9
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic, antihyperlipidemic and antioxidant properties of ethanol extract of Grewia asiatica Linn. bark in alloxan-induced diabetic rats

Abstract: BackgroundInspite of introduction of oral hypoglycemic agents, diabetes and its related complications remains to be a major clinical problem. The aim of this study was to investigate the antidiabetic, antihyperlipidemic and antioxidant activities of Grewia asiatica (Linn) stem bark in alloxan induced diabetic rats.MethodsDiabetes was induced by a single dose of intraperitoneal injection of alloxan (110 mg/kg) in Norwegian Long Evans rats. Ethanol extract of barks from Grewia asiatica (GAE 200 and 400 mg/kg) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 33 publications
2
22
0
3
Order By: Relevance
“…Results exhibited that liver glycogen level was significantly (p < 0.05) decreased in diabetic control as compared to healthy rats (Table 1). Reduction in glycogen synthetase and lower insulin levels are associated with lower glycogen in the liver [22]. Administration of gliclazide and OSE and their combination significantly (p < 0.05) raised the level of liver glycogen resulting in improved glucose metabolism.…”
Section: Effect Of Treatments On Hyperglycemic Parametersmentioning
confidence: 95%
“…Results exhibited that liver glycogen level was significantly (p < 0.05) decreased in diabetic control as compared to healthy rats (Table 1). Reduction in glycogen synthetase and lower insulin levels are associated with lower glycogen in the liver [22]. Administration of gliclazide and OSE and their combination significantly (p < 0.05) raised the level of liver glycogen resulting in improved glucose metabolism.…”
Section: Effect Of Treatments On Hyperglycemic Parametersmentioning
confidence: 95%
“…However, based on the findings of Akhtar, Ihsan‐ul‐Haq, and Mirza (2018), TPC, and TFC in phalsa leaves averaged 30.20 ± 2.0 mg of GAE (gallic acid)/g DW and 9.90 ± 0.50 mg of QE/g DW, respectively. Other studies evaluating phalsa plant total phenolic and flavonoid content found the fruit contained 144.11 mg of GAE/g (TPC) and 4.608 mg of QE/g (TFC) (Srivastava, Kumar, & Vankar, 2012), the stem bark 44.65 ± 3.17 mg of GAE/g DW (TPC) and 3.9 ± 4.65 mg of QE/g DW (TFC) (Khatune, Rahman, Barman, & Wahed, 2016), the roots 11.00 ± 4.38 μg of GAE/ml (TPC), and 16.37 ± 6.43 μg of QE/ml (TFC) (Sharma, Manasi Malgaonkar, Sangvikar, Murthy, & Pawar, 2016), and the flowers 22.19 ± 0.42 µg of GAE/mg DW (TPC) and 52.31 ± 0.10 μg of QE/mg(TFC) (Shukla, Sharma, Pathak, & Bajpai, 2016).…”
Section: Nutritional and Phytochemical Compositionmentioning
confidence: 99%
“…The anti‐microbiological activity of tannins and tannin‐like substances are well documented. Markedly, phalsa have been found to contain tannins in numerous parts of the plant; the fruit, juice leaves, stem, root, and bark of the plant all contain tannins (Akhtar et al, 2018; Babu, Krishna, Ashwini, & Raju, 2017; Islary, Sarmah, & Basumatary, 2016; Khatune et al, 2016).…”
Section: Nutritional and Phytochemical Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic hyperglycemia also termed glucose toxicity has a strong impact of damage on beta-islet cell failure which origins from high glucose-inducing superfluous reactive oxygen species to aggravate oxidative stress in body tissue [ 9 , 10 ]. There are also multiple abnormalities of lipoprotein metabolism due to chronic hyperglycemia, including elevated levels of total cholesterol (TC) and triglycerides (TG) in serum in diabetes [ 11 ]. Liu et al [ 12 ] found that the improvement on glycolipid metabolism was related with the level of oxidative stress in type 2 diabetic model mice.…”
Section: Introductionmentioning
confidence: 99%